Gut Microbiota and Immunity: Possible Role in Sudden Infant Death Syndrome - Goldwater, Paul N. (Frontiers in Immunology, 2015)
The gut microbiome influences the development of the immune system of young mammals; the establishment of a normal gut microbiome is thought to be important for the health of the infant during its early development. As the role of bacteria in the causation of Sudden Infant Death Syndrome (SIDS) is backed by strong evidence, the balance between host immunity and potential bacterial pathogens is likely to be pivotal. Bacterial colonisation of the infant colon is influenced by age, mode of delivery, diet, environment, and antibiotic exposure. The gut microbiome influences several systems including gut integrity and development of the immune system; therefore, gut microflora could be important in protection against bacteria and/or their toxins identified in SIDS infants. The aims of the review are to explore 1) the role of the gut microbiome in relation to the developmentally critical period in which most SIDS cases occur; 2) the concept of an abnormal gut microbiome causing inflammation resulting in transit of bacteria from the lumen into the bloodstream; and 3) clinical, physiological, pathological and microbiological evidence for bacteraemia leading to the final events in SIDS pathogenesis.